THE RELATION OF PAINTING AND CINEMA WITH THEIR SIMILARITIES AND DIFFERENCES - Derya UZUN AYDIN (Fırat University, 2019)
The 19th century, which was undergone the industrial revolution and technological development and proggress, caused some progress and development in visual arts. When we entered 20th century, modernism gained speed and this progress and change have continued until this day. Even though all the change and progress Pictorial Arts kept up with it and continued its progress by reflecting the social and cultural changes of the era. This branch of art, which humanity started to perform even from stone age, brought with it the stylistic novelty. Among the branches of arts, in the sense of visual art, even photo art with the painting art had a big impact on 19th century. Following the invention of photo art, the emergence of cinema art as the 7th branch is considered an important development for these centuries. The branch of cinema art, with its unique style, is a brand new branch and quickly gained progress by taking advantage of technological developmets. The cinema art, which has many similarities and differences with the painting art, many times was refered to as the art of providing cinematic place and time art, the other times it was argued as cinemas are living pictures. In this context, it is understood that painting and cinema are in relation. A few points will come up when mutual relation of cinema art and painting art are studied. The most important among these is the association of image. Cinema, which consists of some frames of pictures, and also the comparative terms like time, place, atmosphere, light-shadow relation in picture art are mentioned and it is understood that both branches of arts are only an illusion show. A visual rishness is achieved by corroborating this common points.